2017
DOI: 10.1242/jeb.166132
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of ionoregulation in the freshwater nymph of the mayfly (Hexagenia rigida)

Abstract: This study investigated ionoregulatory strategies used by freshwater (FW) nymphs of the mayfly Like other FW organisms, nymphs maintain hemolymph ion levels (in mmol l: Na ∼102; Cl ∼84; K ∼6; pH ∼7.35) far in excess of their surroundings. This appears to be accomplished by the combined actions of the alimentary canal, Malpighian tubules (MTs) and tracheal gills. The alimentary canal contributes in a region-specific manner, a view supported by: (1) spatial differences in the activity of basolateral Na/K-ATPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…(Freshwater animals that start to osmoconform above the isoosmotic point do not necessarily increase their internal concentrations of inorganic ions as they may produce organic osmolytes [23,33]). Osmoregulation in aquatic animals is thought to be one of the best understood processes in biology [19], although it is acknowledged that it has been relatively poorly studied in freshwater insects in general [20] and even more so in Ephemeroptera [21]. The introductory biology text books by Reece et al [34], for example, state: 'The energy cost of osmoregulation depends on how different an animal's osmolality is from its surroundings.'…”
Section: The Conventional Model Of Osmoregulation In Freshwatermentioning
confidence: 99%
See 2 more Smart Citations
“…(Freshwater animals that start to osmoconform above the isoosmotic point do not necessarily increase their internal concentrations of inorganic ions as they may produce organic osmolytes [23,33]). Osmoregulation in aquatic animals is thought to be one of the best understood processes in biology [19], although it is acknowledged that it has been relatively poorly studied in freshwater insects in general [20] and even more so in Ephemeroptera [21]. The introductory biology text books by Reece et al [34], for example, state: 'The energy cost of osmoregulation depends on how different an animal's osmolality is from its surroundings.'…”
Section: The Conventional Model Of Osmoregulation In Freshwatermentioning
confidence: 99%
“…Recently, Clements & Kotalik [11] 'seeded' experimental mesocosms with invertebrates from a low salinity site (0.06 -0.07 mS cm 21 ) and then applied various experimental salinity treatments. They observed that salinity of %0.3 mS cm 21 caused declines in the abundance of baetid and heptageniid mayflies and total Ephemeroptera, while Ephemeroptera drift increased. The richness of the insect orders Ephemeroptera, Plecoptera (stoneflies) and Trichoptera (caddisflies), collectively abbreviated to EPT, in southeast Australia [12] and the abundance of Ephemeroptera in Kentucky, USA [13] are reduced monotonically as salinity increases above %0.175-0.2 mS cm 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most air-breathing aquatic insects, such as mosquito larvae, ions and acid-base equivalents are absorbed or excreted directly between the hemolymph and the surroundings through ion-permeable epithelia. This is unlike water-breathing aquatic insects, such as the aquatic nymphs of mayflies, which possess ionocyte-dense tracheal gills for active ion transport (Nowghani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence of rapid evolution of osmoregulatory adaptation in aquatic organisms, which indicates that local adaptation could occur within few generations in the wild [42]. Recent findings showed these adaptation being present in benthic macroinvertebrates facing sublethal salinity levels [43,44]. The mechanisms involve adjustment (i.e.…”
Section: Discussionmentioning
confidence: 99%